Genetic Diversity of Papaya Using Molecular Markers Random Amplified Polymorphic DNA - Aulia, Ewa; Sutrawati, Mimi; Simarmata, Marulak (AGRITROPICA : Journal of Agricultural Sciences, 2024)
Papaya is one type of fruit that is widely consumed and cultivated by the farmer. However, genetic analysis has not been carried out on various types of papaya available on the market. This aims to determine the genetic diversity of papaya plants that can become genetic resources to fullfil food needs and genetic resources for breeders. Genetic analysis was conducted by Random Amplified Polymorphic DNA (RAPD) method using 11 papaya varieties consisting of Calina, Bangkok, Red Pomegranate, Sunrise, Orange Lady, Red Lady, Taiwan, Arum, Miba, Golden, and Local and using 15 RAPD primers consisting of OPA-1, OPA-2, OPA-8, OPA-16, OPC-4, OPC-11, OPC-13, OPC-20, OPD-20, OPE-2, OPE-6, OPE-11, OPE-14, OPM-6, and OPY-15. PCR-RAPD results were translated into binary data and then cluster analysis was conducted using the Unweighted Pair-Group Method Arithmetic (UPGMA) method using the Numerical Taxonomy and Multivariate System (NTSYS) program. The PCR-RAPD results of 11 papaya varieties successfully amplified 8 out of 15 primers that formed 112 DNA bands with 85 polymorphic bands. Genetic diversity analysis showed the results at 90% similarity coefficient formed 9 groups. Group 1 consists of Bangkok and Sunrise varieties. Group 2 consists of Red Pomegranate and Arum varieties. Groups 3 to 9 consisted of Calina, Miba, Local, Golden, Orange Lady, Red Lady, and Taiwan varieties, respectively.